2020
DOI: 10.3390/diagnostics10090608
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Usefulness of CO-RADS for Chest CT in Patients Suspected of Having COVID-19

Abstract: The purpose of this study was to use the Coronavirus Disease 2019 (COVID-19) Reporting and Data System (CO-RADS) to evaluate the chest computed tomography (CT) images of patients suspected of having COVID-19, and to investigate its diagnostic performance and interobserver agreement. The Dutch Radiological Society developed CO-RADS as a diagnostic indicator for assessing suspicion of lung involvement of COVID-19 on a scale of 1 (very low) to 5 (very high). We investigated retrospectively 154 adult patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
61
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 21 publications
(27 reference statements)
9
61
1
4
Order By: Relevance
“…For the CO-RADS, substantial to almost perfect interobserver agreement has been reported, with ĸ values of 0.648 to 0.773 ( 8 ) and intraclass correlation coefficients of 0.800 to 0.874 ( 20 ). For the RSNA classification system, moderate to substantial interobserver agreement has been reported, with ĸ values of 0.500 ( 23 ) and of 0.570 to 0.663 ( 8 ).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…For the CO-RADS, substantial to almost perfect interobserver agreement has been reported, with ĸ values of 0.648 to 0.773 ( 8 ) and intraclass correlation coefficients of 0.800 to 0.874 ( 20 ). For the RSNA classification system, moderate to substantial interobserver agreement has been reported, with ĸ values of 0.500 ( 23 ) and of 0.570 to 0.663 ( 8 ).…”
Section: Resultsmentioning
confidence: 94%
“…After reading the full text of the 14 studies, three studies ( 16 - 18 ) were excluded because the diagnostic performance of either CO-RADS or the RSNA classification system was not investigated, one study ( 5 ) was excluded because no data on a per-patient level were reported, and another study ( 19 ) was excluded because there were overlapping data with another study ( 8 ) which comprised a larger number of patients. Nine studies were eventually included ( 8 , 20 - 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations